The Politics of Social Inclusion Bridging Knowledge and Policies Towards Social Change - Koehler, Gabriele; Cimadamore, Alberto D; Kiwan, Fadia; Monreal Gonzalez, Pedro Manuel
This volume looks at concepts and processes of social exclusion and social inclusion. It traces a number of discourses, all of them routed in a relational power analysis, examining them in the context of the UN Agenda for Sustainable Development 2030 with its commitment to "leave no one behind." The book combines analysis that is fundamentally critical of the rhetoric of social inclusion in academic and UN discourse with narratives of social exclusion processes and social inclusion contestation, based on ethnographic field research findings in Bogota, Kingston, Port-au-Prince, Kampala, Beijing, Chongqing, Mumbai, Delhi, and villages in Northern India. As a result, it contributes to revealing the politics of social inclusion, offering policy proposals towards overcoming exclusions